Reserved Seats on Japan's Supreme Court - Lawrence Repeta (Washington University Law Review, 2011)
The Article examines the decision on the allocation of seats to private attorneys and scholars in the Japanese Supreme Court. It outlines the reallocation of reserved seats during the term of Chief Justice Ishida Kazuto from 1969 to 1973. It stresses the institutionalization of an appointment pattern designed to limit the individual rights declared in the Japanese Constitution.
Keywords: Constitutional law -- Japan; Judicial independence -- Japan; Freedom of speech -- Japan; Japan. Daishin' in